Irish Soccer Migrants : a Social and Cultural History - Curran, Conor (Book collections on Project MUSE., 2017)
This book looks at the experiences and achievement levels of Irish-born post-war soccer migrants to Britain. It draws on interviews with thirty Irish-born soccer players, each of whom has played league soccer in England or Scotland, using two players each from the Republic and Northern Ireland per decade. This is the first book to use these migrants as a quantitative source, and to illustrate their experiences. It draws on extensive research conducted through a database of every Irish born player who played league soccer in England or Scotland between 1945 and 2010. An examination of the birthplaces of these players is offered along with the reasons for their geographical diversity. It discusses their childhood influences and assesses the recruitment process and identifies the clubs which have produced the most players. The impact of the Northern Ireland Troubles on the migration of Northern Ireland-born players is discussed while the attitudes of a number of players to this are assessed. An assessment of their working conditions and the culture of professional soccer is given while the book also examines the changing nature of the post-playing careers of these players. In locating the study of Irish soccer migrants within the study of Irish migration to Britain and comparing the experience of Irish-born soccer players with those from other nations, this book is the first of its kind.